Pengaruh Model Pembelajaran 3 M (Meniru, Mengolah dan Mengembangkan) terhadap Kemampuan Menulis Surat Pribadi pada Siswa Kelas VII - Ester Romaito Malau; Frinawaty Lestarina Barus (ENGGANG: Jurnal Pendidikan, Bahasa, Sastra, Seni, dan Budaya, 2024)
This study aims to determine the effect of the 3M learning model (Imitating, Processing and Developing) on ​​the ability to write personal letters in class VII students of SMP Negeri 4 Medan which consists of 11 classes with a total of 344 people. The sample in this study consisted of 2 classes, namely the control class and the experimental class. The control class (class VII-7) consisted of 30 people and the experimental class (VII-5) consisted of 30 people. The research method used is an experimental research method with the type of post-test only control group design using a quantitative approach. The mean post-test score of students in the control class was 51, which was in the less category, while the mean post-test value of students in the experimental class was 87.66, which was in the very good category and had fulfilled the KKM. Based on the results of the analysis, it is obtained t count = 14.754 and t table = 1.699, so that it is obtained if t count ˃ t table or 14.754 ˃ 1.699. So, it can be concluded that Ho is rejected and Ha is accepted, meaning that the application of the 3 M Learning Model (Imitating, Processing, and Developing) has an effect on the ability to write personal letters for class VII students of SMP Negeri 4 Medan.